Mitigation for minors: exploring the nuances of social constructs and legal status in structuring sentences for youthful offenders - Kurlychek, Megan C. (Punishment & society, 2018)
New York State is one of only two states in the nation that processes all 16- and 17-year-old defendants as adults. Contrary to this seemingly punitive stance, the state also maintains a Youthful Offender Statute that requires mitigated punishments for youths up to their 19th birthday upon court designation of youthful offender status. This study empirically examines the individual and combined impact of the social status of being a “minor” and the legally awarded status of being designated a youthful offender, upon adult court sentencing decisions framing the discussion within broader conceptualizations of youthfulness, culpability, and punishment. Utilizing a population of all youths ages 16-21 whose cases were disposed in New York between 2000 and 2006, this study finds the legally defined status of youthful offender to provide much greater mitigation at sentencing than the more general social status of being a minor. Findings are discussed as they relate to categorical and individualized assessments of culpability. In addition, as the study finds individualized assessments of culpability to be related to factors such as gender and race, broader implications for the role of court assigned statuses and mitigation of punishment are offered.